2021
DOI: 10.1186/s43141-021-00165-8
|View full text |Cite|
|
Sign up to set email alerts
|

Defining the molecular pathology and consequent phenotypes in Egyptian HB patients

Abstract: Background Hemophilia B (HB) (also known as Christmas disease) is a rare X-linked recessive disorder characterized by spontaneous or prolonged hemorrhages caused by mutations in Factor 9 (F9) gene leading to deficient or defective coagulation F9. Our study aimed at identifying the causative mutations within a sample of HB Egyptian patients. The present study comprised clinical data of eleven HB patients descending from six unrelated families and a seventh family including a carrier mother with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In line with literature reports, the present study confirms the well-known frequent genetic defect of HA and HB, where the null allele (large deletion, insertion/deletion mutations, nonsense, and gene rearrangements principally inversion of intron 22) was responsible for the most frequent genetic abnormalities in severe HA (10 out of 26 severe forms, 38.4%), whereas missense mutations have been found in the majority of patients with moderate (3 out of 5, 60%) and mild forms of the disease (5 out of 7, 71.4%) and comprise the most frequent molecular defect in HB (>50% of all reported mutations) (Supplemental Tables 1 and 2, online version). 7,17,19,20,22,23 Our study also in agreement with previously published data 3,24 found that the risk of developing inhibitors was much less frequent in HB patients compared to HA (5.1% vs 25%, respectively), and the risk was allied mostly in severely affected patients except for 2 mild HA cases (Supplemental Tables 1 and 2, online version), thus supporting the assumption that the higher prevalence of the less severe missense mutations in HB compared to HA provides a potential biological reason for explaining the milder disease phenotype regarding bleeding severity and inhibitor risk in HB versus HA. 3 It is well known that the risk for inhibitor development to factor replacement therapy is related to several factors including the type and location of genetic defect, where variants with gross defects, such as Out of all cases, 1 case was positive for the factor inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with literature reports, the present study confirms the well-known frequent genetic defect of HA and HB, where the null allele (large deletion, insertion/deletion mutations, nonsense, and gene rearrangements principally inversion of intron 22) was responsible for the most frequent genetic abnormalities in severe HA (10 out of 26 severe forms, 38.4%), whereas missense mutations have been found in the majority of patients with moderate (3 out of 5, 60%) and mild forms of the disease (5 out of 7, 71.4%) and comprise the most frequent molecular defect in HB (>50% of all reported mutations) (Supplemental Tables 1 and 2, online version). 7,17,19,20,22,23 Our study also in agreement with previously published data 3,24 found that the risk of developing inhibitors was much less frequent in HB patients compared to HA (5.1% vs 25%, respectively), and the risk was allied mostly in severely affected patients except for 2 mild HA cases (Supplemental Tables 1 and 2, online version), thus supporting the assumption that the higher prevalence of the less severe missense mutations in HB compared to HA provides a potential biological reason for explaining the milder disease phenotype regarding bleeding severity and inhibitor risk in HB versus HA. 3 It is well known that the risk for inhibitor development to factor replacement therapy is related to several factors including the type and location of genetic defect, where variants with gross defects, such as Out of all cases, 1 case was positive for the factor inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In line with literature reports, the present study confirms the well-known frequent genetic defect of HA and HB, where the null allele (large deletion, insertion/deletion mutations, nonsense, and gene rearrangements principally inversion of intron 22) was responsible for the most frequent genetic abnormalities in severe HA (10 out of 26 severe forms, 38.4%), whereas missense mutations have been found in the majority of patients with moderate (3 out of 5, 60%) and mild forms of the disease (5 out of 7, 71.4%) and comprise the most frequent molecular defect in HB (>50% of all reported mutations) ( Supplemental Tables 1 and 2 , online version). 7 , 17 , 19 , 20 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%